Pediatric pedunculated perianal problems - R.L. Massoumi; L.N. Parsons; J.A. Jarzembowski; A.J. Wagner (Elsevier, 2016)
Congenital perianal masses, distinct from sacrococcygeal teratomas, are a rare entity and are minimally reported in literature. A retrospective chart review was conducted of all patients who presented to the Children's Hospital of Wisconsin (CHW) with a benign pedunculated perianal mass between April 2014 and June 2015. Three patients fulfilling these criteria underwent elective resection either under general or local anesthesia. The first patient's mass was diagnosed as a benign acrochordon, or skin tag. The midline location of this mass prompted a spinal MRI revealing a low-lying conus and fibrolipoma of the filum terminale. The patient underwent prophylactic laminectomy and transection of the filum terminale and he currently remains asymptomatic. The second patient was found to have a hamartomatous polyp and later developed scrotal and perirectal vascular malformations and was treated successfully with topical timolol. Our third patient presented with a hamartomatous lesion and underwent a colonoscopy and stool studies, both of which were negative. We present these cases to bring awareness to this clinically important entity and to the associated anomalies and work-up that should be considered.